Investigation of the gut parasitic community composition in Manis pentadactyla and Manis javanica based on high-throughput amplicon sequencing - Chen, Sitong; Wang, Xianghe; Liu, Xinyu; Xie, Meiling; An, Fuyu; Wang, Kai; Zhang, Zhenquan; Zhou, Shuo; Hua, Yan (Frontiers in Veterinary Science, 2025)
IntroductionThe critically endangered Manis pentadactyla and Manis javanica are increasingly threatened by parasitic infections, with gastrointestinal nematodes and protozoan parasites particularly prominent.MethodsIn this study, 72 fecal samples were collected from captive M. javanica and M. pentadactyla housed at the Guangdong Wildlife Monitoring and Rescue Center in China. High-throughput amplicon sequencing targeting the V9 region of the 18S rRNA gene was employed to investigate the community composition and diversity of their gastrointestinal parasite communities.ResultsOur results revealed significant differences in the composition of parasitic communities across species and sex groups. Several potentially pathogenic helminths and protozoa were identified. The helminths included Rhabditida, Moniliformida, and Diplogasterida. Protozoan taxa such as Eimeria, Cryptosporidium, and other free-living protozoa such as Acanthamoeba, Colpoda, Vermamoeba, Bicosoecida, and Trinema were found to be highly abundant and widely distributed. While these free-living protozoa are commonly found in environmental samples, there is no solid evidence of their parasitic or pathogenic role in pangolins.DiscussionThis study systematically characterized the gastrointestinal parasitic communities in captive M. pentadactyla and M. javanica. Notably, Apicomplexa and Nematoda were found to be dominant and likely represented the most susceptible parasitic groups in pangolins under captive conditions. These findings offer valuable insights for the diagnosis, treatment, and health management of parasitic infections in pangolin conservation.